Evaluation of nutrient conditions in open hydroponic system based on tomato production - Rácz, Istvánné (Acta Agraria Debreceniensis, 2007)
Monoculture caused a gradual decline of soil conditions, while nematodes and salt accumulation stimulated the growers to choose alternative practices, such as soilless cultures, which proved their value in Western Europe. Exact statistics are lacking, but estimates deal with approximately 300-400 hectares of vegetable on rock wool, whereas other substrates of soilless culture may multiply this number. Real perspectives are attributed to the forced production of pepper, tomato and cucumber. Vegetable production in greenhouses may impair the ecological balance of the environment substantially as far as being uncontrolled. Soilless cultures especially should be handled thoughtfully. A fraction of the nutrients administered, more than 25-30%, is doomed to be lost in an open system, and the resulting ecological risk is accompanied with increasing costs of the production. In Hungary, the quantity of nutrient elements in drainage water is unknown, et all. Connecting the production results with chemical analysis, we gain more information about it. You can see a mathematical method for evaluation of nutrient and water conditions in tomato hydroponics production.